Comparison of nuclear DNA with whole cell DNA isolated from Neurospora crassa - S. K. Dutta; I. Gbadamosi; C. Chambers; D. K. Mukhopadhyay (Fungal Genetics Reports, 1980)
Comparison of nuclear DNA with whole cell DNA isolated from Neurospora